ATM Substrate Chk2-interacting Zn(2+) Finger (ASCIZ) Is a Bi-functional Transcriptional Activator and Feedback Sensor in the Regulation of Dynein Light Chain (DYNLL1) Expression - Jurado, Sabine (American Society for Biochemistry and Molecular Biology, 2012)
The highly conserved DYNLL1 (LC8) protein was originally discovered as a light chain of the dynein motor complex, but is increasingly emerging as a sequence-specific regulator of protein dimerization with hundreds of targets and wide-ranging cellular functions. Despite its important roles, DYNLL1's own regulation remains poorly understood. Here we identify ASCIZ (ATMIN/ZNF822), an essential Zn(2+) finger protein with dual roles in the DNA base damage response and as a developmental transcription factor, as a conserved regulator of Dynll1 gene expression. DYNLL1 levels are reduced by ∼10-fold in the absence of ASCIZ in human, mouse and chicken cells. ASCIZ binds directly to the Dynll1 promoter and regulates its activity in a Zn(2+) finger-dependent manner. DYNLL1 protein in turn interacts with ten binding sites in the ASCIZ transcription activation domain, and high DYNLL1 levels inhibit the transcriptional activity of ASCIZ. In addition, DYNLL1 was also required for DNA damage-induced ASCIZ focus formation. The dual ability of ASCIZ to activate Dynll1 gene expression and to sense free DYNLL1 protein levels enables a simple dynamic feedback loop to adjust DYNLL1 levels to cellular needs. The ASCIZ-DYNLL1 feedback loop represents a novel mechanism for auto-regulation of gene expression, where the gene product directly inhibits the transcriptional activator while bound at its own promoter.